2018
DOI: 10.1007/s10620-018-5268-0
|View full text |Cite
|
Sign up to set email alerts
|

Silybin Alleviates Hepatic Steatosis and Fibrosis in NASH Mice by Inhibiting Oxidative Stress and Involvement with the Nf-κB Pathway

Abstract: Silybin was effective in preventing the MCD-induced increases in hepatic steatosis, fibrosis and inflammation. The effect was related to alteration of lipid metabolism-related gene expression, activation of the Nrf2 pathway and inhibition of the NF-κB signaling pathway in the NASH liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…In addition, Wang's team reported that silibinin at 200 mg/kg inhibited thioacetamide- (TAA-) induced liver injury and fibrosis by decreasing α -SMA and inflammatory cytokines IL-1 β , IL-6, and TNF- α levels, which was associated with the upregulation of CYP3A via pregnane X receptor (PXR) [ 18 ]. Silibinin at a dose of 105 mg/kg was effective for preventing hepatic steatosis and fibrosis in a NASH mouse model through regulating lipid metabolism-related gene expression, activating Nrf2, and inhibiting the NF- κ B signaling pathway [ 19 ]. In an in vitro study, 25–50 μ mol/L silybin dose-dependently inhibited the activation of HSC proliferation, cell motility, and ECM deposition through anti-inflammatory activities [ 20 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…In addition, Wang's team reported that silibinin at 200 mg/kg inhibited thioacetamide- (TAA-) induced liver injury and fibrosis by decreasing α -SMA and inflammatory cytokines IL-1 β , IL-6, and TNF- α levels, which was associated with the upregulation of CYP3A via pregnane X receptor (PXR) [ 18 ]. Silibinin at a dose of 105 mg/kg was effective for preventing hepatic steatosis and fibrosis in a NASH mouse model through regulating lipid metabolism-related gene expression, activating Nrf2, and inhibiting the NF- κ B signaling pathway [ 19 ]. In an in vitro study, 25–50 μ mol/L silybin dose-dependently inhibited the activation of HSC proliferation, cell motility, and ECM deposition through anti-inflammatory activities [ 20 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Activation of hepatic stellate cells (HSCs) involves the transition from a quiescent to a proliferative, migratory and fibrogenic phenotype (i.e., myofibroblast) which is characteristic of liver fibrogenesis. To date, multiple cell-surface, cytoplasmic and nuclear molecular signals and pathways have been reported to modulate HSC activation, including cytokines ( Syn et al, 2011 , 2012 ); adipocytokines ( Saxena and Anania, 2015 ; Coombes et al, 2016 ); Toll-like receptors (TLRs) ( Chou et al, 2012 ; Seo et al, 2016 ); Interleukins (ILs) ( Jiao et al, 2016 ); collagen receptors ( Liu et al, 2017 ); nuclear receptors ( Beaven et al, 2011 ; Ding et al, 2013 ; Li et al, 2014 ; Palumbo-Zerr et al, 2015 ; Duran et al, 2016 ); G protein-coupled receptors (GPCRs) ( Li et al, 2015 , 2016a ; Le et al, 2018 ); autophagy ( Thoen et al, 2011 , 2012 ; Hernández-Gea and Friedman, 2012 ; Hernández-Gea et al, 2012 ); endoplasmic reticulum stress ( Hernández-Gea et al, 2013 ; Koo et al, 2016 ); oxidative stress ( Lan et al, 2015 ; Ou et al, 2018 ); epigenetics ( Coll et al, 2015 ; Hyun et al, 2016 ; Kweon et al, 2016 ; Huang et al, 2018 ; Zheng et al, 2018 ); cell metabolism ( Nwosu et al, 2016 ; Du et al, 2018 ; Franko et al, 2018 ; Zhang et al, 2018 ), etc. In addition, extracellular/paracrine signals from resident and inflammatory cells including hepatocytes ( Zhan et al, 2006 ), macrophages ( Pradere et al, 2013 ), natural killer cells ( Glässner et al, 2012 ), natural killer T cells ( Wehr et al, 2013 ), liver sinusoidal endothelial cells (LSECs) ( Xie et al, 2012 ), platelets ( Kurokawa et al, 2016 ), and B cells ( Thapa et al, 2015 ) further promote HSC activation.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest the possible ameliorating effect on non-alcoholic steatohepatitis (NASH) [155]. The investigations conducted by Ouet et al [156] on male C57BL/6 mice revealed, after 8 weeks of a methionine-choline-deficient diet, the induction of NASH. The oral ingestion of silybin significantly inhibited the gene expression associated with lipid metabolism, inflammation-related gene expression, and the NF-κB signaling pathway.…”
Section: Nrf2 Activated By Silymarin and Flavolignans: Promising Thermentioning
confidence: 89%